Coastal Greenland air temperature extremes and trends 1890–2010: annual and monthly analysis. (3rd July 2013) - Mernild, Sebastian H.; Hanna, Edward; Yde, Jacob C.; Cappelen, John; Malmros, Jeppe K.
ABSTRACT We use observed air temperature data series from 14 meteorological stations in coastal Greenland (located all around the Greenland Ice Sheet) for 1960–2010, where long‐term records for five of the stations extend back to 1890, to illustrate the annual and monthly temporal and spatial distribution of temperature extremes, with the main focus on the latest decade 2001–2010 (2000s). We find that the 2000s had the highest number of mean annual air temperature (MAAT) warm extremes, and the 1890s the highest number of cold extremes, and that a high (low) positive North Atlantic Oscillation (NAO) Index equals a high number of cold (warm) extreme events. For the 2000s the number of warm extremes was significantly higher by around 50% than the number in the 1940s (the early twentieth century warm period): the latter being the decade with the second highest occurrence of MAAT warm extremes. Since 1960, based on MAAT the number of cold extremes has overall decreased on the decadal timescale, besides a peak in 1980s, while warm extremes have increased, leading to a higher occurrence of extremes (cold plus warm extremes): an almost similar pattern occurred for monthly mean temperatures and monthly mean daily maximum and minimum temperature datasets. Furthermore, a division of Greenland into east and west sectors shows that the occurrence of cold (warm) extremes was more pronounced in the East than in the West in the 1960s and 1970s (mid‐1980s to the 2000s).